Investigating the Impact of Globalization on Environmental Degradation in Kazakhstan - Primbetova, Madina; Sharipov, Kongratbay; Allayarov, Piratdin; Haq, Ihtisham ul (Frontiers in Energy Research, 2022)
As a consequence of globalization, the world's economies are merging; nonetheless, concerns about how globalization trends may harm the environment locally and worldwide are growing. The globalization-environment nexus has now become a contentious issue among policymakers. As a result, several empirical research studies on the globalization-environment nexus have been conducted. In the context of the environmental Kuznets curve theory, this study explores the influence of globalization on environmental deterioration in Kazakhstan (EKC). Furthermore, energy is a control variable in this research. Unit roots and structural break are used to solve the issue of non-stationarity in time series. The autoregressive distributed lagged (ARDL) model is used in this research for long run relationships between variables as well as to estimate long run and short run coefficients. Income, energy, and globalization are discovered to have a long-term link. Furthermore, the findings revealed that long-term environmental deterioration was exacerbated by economic, political, and social globalization, since these factors were shown to have a positive impact on carbon emissions in Kazakhstan. Energy is to blame for environmental damage both in the short and long term. Furthermore, this research reveals that the EKC theory exists in Kazakhstan. On the basis of the findings, policy suggestions are made.